Peran Lembaga Penjamin Simpanan dalam Memberikan Perlindungan Nasabah Pada PT. Pembiayaan Bank Syariah Puduarta Insani - Amini, Aisyah (Al-Muhtarifin: Islamic Banking and Islamic Economic Journal, 2024)
This research was conducted to find out about the understanding and knowledge of customers regarding the function of the Deposit Insurance Corporation (LPS) and the form of protection carried out by LPS in handling customer deposits made at PT. Puduarta Insani Islamic People's Financing Bank. The method used in this research is a qualitative method with a descriptive approach, the source of data in this study comes from primary data obtained from interviews with employees and customers of PT BPRS Puduarta Insani. The results of this study are after conducting interviews, customers do not know and understand exactly the function of the Deposit Insurance Corporation and until now customers feel that LPS is not so necessary because their deposit funds are safe and for efforts made by LPS in providing customer protection is to provide guarantees to depositors. With the existence of LPS, if there is a bank that is experiencing business difficulties and then its business is revoked and liquidated, the position of the customer will still be guaranteed.Keyword: Deposit Insurance Corporation, Protection, Customers, and Knowledge